The Planning and Implementation of Manufacturing Execution System (MES) – Requirements and Derived Results for Material Management in Case Company Context - Heikkilä, Tiia (My University, 2018)
The purpose of this thesis is to examine what should be taken into account from material management point of view when planning and implementing Manufacturing Execution System (MES) and how it affects industrial material management context in a case company. To reach this purpose, both theoretical and empirical aspects are observed in this study. First the study presents the theoretical background of MES implementation, then material management as part of organization is examined, and after that the framework of material management performance measurement is investigated. In the empirical part the analysis is divided into two parts; before and after MES implementation. In the first part (before MES) the material management is presented as it is organized in a case company, its challenges are reviewed and potential benefits of MES for those challenges are examined. The performance of material management is also analysed as well as the requirements and changes that need to be done in order to maximize the utilization of MES. In the second part (after MES), the planned benefits and performance are reviewed as well as the planned changes, so that it can be evaluated whatever the targets of MES are reached as planned. In addition the challenges of implementation phase and proposals for further MES development are investigated. The results of the study was a coherent overview to the notions and requirements that should be noted and analysed when a company is planning to implement MES and what it means from material management point of view. First of all, attention should be paid to the specific characteristics of the industry and company requirements as well as to the relationship between a customer and solution supplier so that the implementation can be carried out successfully. The results show that the current way-of-workings needs to be analysed enough detail level and the benefits that MES could provide to be reviewed. In addition, targets need to be set so that the progress of the implementation can be reviewed and in case of need corrective actions to be made so that the targets could be reached. In this study the practical level results of MES implementation were investigated and analysed before and after the implementation from case company point of view. The results show that even though all the planned benefits of MES for efficient material management weren’t reached during this study scope, the implementation was accomplished in a good manner despite the multiple challenges and the planned benefits of MES for material management are seen reachable.
Keywords: MES; Material management; Performance Measurement; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|